PEMAKNAAN KHALAYAK TERHADAP KEMARAHAN PEREMPUAN DALAM DRAMA KOREA THE GLORY - Ardani, Fransisca; Nur Suryanto Gono, Joyo; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Women's anger expressions are often debated and tend to be rejected as irrational. On the other hand, the expression of anger of women who are victims of bullying is highlighted as an interesting aspect of the Korean drama The Glory, which is expressed through acts of revenge against the perpetrators who bullied them.The Glory was liked and watched by many viewers and also received various comments regarding the expression of anger of women who were victims of bullying and acts of bullying on social media. This research aims to describe the audience's interpretation of women's anger in the Korean drama The Glory. This research uses active audience theory, audience reception theory, and the semiotic analysis method by John Fiske to see the dominant meaning or preferred reading as well as the reception analysis method by Stuart Hall to determine the informant's position of meaning. The results of this research show that the five male and female informants, with different backgrounds and experiences, show a tendency for informants to be in a negotiated position regarding the dominant meaning displayed in the text. Two informants who had been victims of bullying were in a dominant position in interpreting expressions of anger in the Korean drama The Glory. On the other hand, three informants, namely one informant who had contact with the victim of bullying, were in a negotiating position and two informants who were not or had never been victims of bullying were in a negotiating position. Thus, the findings of this study found that there was a disclosure of women's power regarding women's expressions of anger. This research also shows that there is a film strategy by showing women's expressions of anger as victims of bullying that can be accepted by the audience, namely by taking revenge in a strategic and tactical way based on the crimes committed by the perpetrators of the bullying.